The Development of Post-Soviet Health Systems: A Mixed Methods Historical Case Study - Hotchner, Blaser Rebecca (Department of Public Health and Family Medicine, 2023)
After independence, post-Soviet countries embarked on various trajectories of health system development, some more successfully than others. Several countries throughout the region, limited by political and economic constraints, continue to struggle with health systems strengthening, leading to negative downstream effects on population health. For countries further behind in their development trajectories, learning from successful reform experiences could support health policymaking, though health policy and systems research on this topic is scarce, particularly in the former Soviet Union. To begin to address this gap, a mixed-methods historical case study was conducted, analysing and comparing two post-Soviet health system development experiences—in Estonia and Moldova. The cases were selected on the basis of specific differentiators, to capture a wider range of regional experiences. The country case studies focused analysis on four health systems areas, in accordance with the European Observatory on Health Systems and Policies' Health Systems in Transition framework—namely organisation and governance, financing, physical and human resources, and provision of services. Quantitative and qualitative data were synthesized, with quantitative data including select demographic, macroeconomic, and population health indicators, and qualitative data including thematic analysis of policy and research materials. The study utilised a combined complex adaptive systems and historical institutionalist perspective. The subsequent cross-country comparative analysis sought to identify ‘good health at low cost' practices appropriate to a post-Soviet context, with the aim of drawing lessons towards health systems strengthening in the broader region. Study findings suggest that political commitment to the health system development project is key; specific policies around revenue collection and pooling mechanisms are important; privatisation should be applied strategically; a holistic strategy around service provision is necessary, balancing hospital, primary health care, and public health reform; engaging external organisations in terms of financial and technical assistance can be advantageous; and health worker supply issues must be addressed. Given the contextual dissimilarities between the two country case studies, overlapping reform trends are likely indicative of regional specificities. Such knowledge can be leveraged to benefit other post-Soviet states, towards optimal health system development along the post-Soviet historical pathway.